Ayurvedic Approach towards Management of Acid Reflux Disorder - Warghade, Sahebrao D. (Asian Journal of Biological and Life Sciences, 2025)
Background: GERD (Urdhwaga Amlapitta) and its Ayurvedic management are discussed via a case report of a 21-year-old female with severe reflux and hemorrhagic gastritis. Intervention: Pitta Shamaka Chikitsa, herbomineral drugs, and lifestyle/diet changes. Result: Marked symptom relief within three weeks with no side effects. Conclusion: Ayurveda protocols can offer effective management for refractory GERD cases.
Keywords: GERD; Amlapitta; Ayurveda